2014
DOI: 10.1002/cbdv.201400100
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Antioxidant Activities of Fourteen Mentha Essential Oils and Their Components

Abstract: The essential oils of 14 species and hybrids, respectively, of the genus Mentha were examined for their antioxidant capacity in the ABTS (2,2'-azinobis(3-ethylbenzothiazoline-6-sulfonic acid)) assay and in a lipid-peroxidation (LPO) assay. The ABTS(.+) -scavenging capacity of pure essential-oil components and mixtures of them was also tested. In both assays, Mentha×dumetorum (classification not fully confirmed), Mentha suaveolens, and Mentha×villosa (classification not fully confirmed) showed the highest antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…El-Askary et al [43] reported a potent antioxidant activity in vivo, which was about 96% relative to vitamin E, while Ferreira et al [44] described the AChE inhibitory capacity as higher than 50% in the essential oil fraction of M. suaveolens . The antioxidant capacity in this case is due to piperitone oxide being present at 88% [45]. Other authors have reported no relevant antioxidant activity for this species [46].…”
Section: Antioxidant Propertiesmentioning
confidence: 93%
“…El-Askary et al [43] reported a potent antioxidant activity in vivo, which was about 96% relative to vitamin E, while Ferreira et al [44] described the AChE inhibitory capacity as higher than 50% in the essential oil fraction of M. suaveolens . The antioxidant capacity in this case is due to piperitone oxide being present at 88% [45]. Other authors have reported no relevant antioxidant activity for this species [46].…”
Section: Antioxidant Propertiesmentioning
confidence: 93%
“…Despite ␣-tocopherol, BHT and ascorbic acid (only active in DPPH assays) were more effective than the essential oil, it is feasible to use it as antioxidant additive for food and cosmetic industries. Sitzmann et al (2014) described the antioxidant activity of several Mentha species. According to this study, some compounds including menthone and linalool could be participating in the antioxidant effects of C. macrostemum var.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…The antioxidant activities of Hawk tea volatile oils were associated with a significant presence of major compounds such as 1,8‐cineole and limonene. However, the antioxidant activity of an essential oil cannot be attributed only to these main compounds, as minor compounds are likely to play a significant role in the antioxidant activity, and synergistic effects have also been reported …”
Section: Resultsmentioning
confidence: 99%